Mobilidade corporativa, relações de hospitalidade entre Stakeholders e a nova classe média: um estudo de casos múltiplos - GOLDENBERG, Cintia (2016)
This research addresses the corporate mobility, the displacement of people motivated by work on behalf of an organization and the relationships between different stakeholders participating in this process. This mobility is becoming increasingly present in the national and international business landscape, driven by globalization, the internationalization of the economy and the growth of emerging economies. In these countries, the entry of large numbers of people in the middle class brought with it a new profile of employee and corporate traveler. The research question is: how does the management of hospitality experience in the provision of services in corporate mobility contributes to competitiveness? Within this context, this research has as main objective to understand the relationship between the management of the hospitality experience, the provision of services in corporate mobility and competitiveness. It also aims to know the demands of the emerging middle class as business traveler; understand the hospitality in the relationship between the stakeholders involved in the corporate mobility of the emerging middle class and examine how the host company meets the specific needs of the emerging middle class traveler on the corporate mobility. Based on the described objectives, the research question is: how does the management of hospitality experience in the provision of services in corporate mobility contributes to competitiveness? Three propositions will be tested: (P1) identifying the demands of the emerging middle class travelers with regard to the dimensions of hospitality facilitates the correct provision of services in the corporate mobility process; (P2) there is a hospitality relationship between the stakeholders of the enterprise mobility process and the organization and (P3) as the organization assumes the host role in the corporate mobility process of the emerging middle class and meets the specific needs of these travelers it becomes more competitive. The research methodology is an empirical, qualitative- quantitative and exploratory research, adopting the multiple case study method as proposed by Yin (2005). The collection of evidences will be held through bibliographic research, documents and through interviews and survey. The proposed research protocol was developed with the characterization method proposed by Bardin (1977), which will serve as a basis for further content analysis of the content generated by the interviews and survey.